2019
DOI: 10.1590/0103-8478cr20180247
|View full text |Cite
|
Sign up to set email alerts
|

Oral glucosamine and chondroitin sulfate on synovial fluid biomarkers from osteoarthritic equine joints

Abstract: Several studies, mainly in vitro, have shown that chondroitin sulfate (CS) and glucosamine (GlcN) do have chondro protective and anti-inflammatory actions. The aim of the present study was to investigate whether oral CS/GlcN supplementation has effects on the CS, hyaluronic acid (HA) and prostaglandin E2 (PGE2) concentrations on synovial fluid of equine osteoarthritic joints. Horses with mild osteoarthritis (OA) in tibiotarsal joint received daily PO doses of CS and GlcN (2.8/3.1 g) for 25 days. Synovial fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Since this treatment increases the production of chondral extracellular matrix and support the normalization of joint homeostasis [ 8 ], and observing the improvement in GT, it can be suggested that the surgically induced osteoarthritis may have influenced the measurement of synovial glycosaminoglycans. Previous studies [ 9 , 10 ] reported a systemic distribution of CS and GlcN after oral administration in doses even lower than the one used in this experimentation, through urinary excretion and measurement of glycosaminoglycans in the synovial fluid, indicating that, although not verified in this study, the systemic distribution probably also occurred. Likewise, their anti-inflammatory potential has also been reported [ 16 ].…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…Since this treatment increases the production of chondral extracellular matrix and support the normalization of joint homeostasis [ 8 ], and observing the improvement in GT, it can be suggested that the surgically induced osteoarthritis may have influenced the measurement of synovial glycosaminoglycans. Previous studies [ 9 , 10 ] reported a systemic distribution of CS and GlcN after oral administration in doses even lower than the one used in this experimentation, through urinary excretion and measurement of glycosaminoglycans in the synovial fluid, indicating that, although not verified in this study, the systemic distribution probably also occurred. Likewise, their anti-inflammatory potential has also been reported [ 16 ].…”
Section: Discussionmentioning
confidence: 48%
“…In the present study, the chondral defect was created with surgical instruments and the oral treatment at the dose used may not have been effective to decrease or inhibit extracellular matrix degradation with the type of induction used. However, as preventive and support treatment this compound is may be important, considering the other beneficial effects demonstrated from T0 to T4 in the GT and also reported in the literature [ 8 10 , 12 , 25 ].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations